Translating Woman: Reading the Female through the Male - Henitiuk, Valerie (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1999)
AbstractFeminist literary criticism has argued that our understanding of literary paradigms, metaphors, and meaning in general is profoundly affected by the gender of both author and audience. Critics of this school posit that a woman's experience comprises unique perceptions and emotions, and that women and men do not inhabit an identical world, or at the very least do not view it identically, in that sexual difference as a social construct has implications for how one interprets as well as how one is interpreted. This article discusses the nature of the text/reader transaction, and the effect on the dialogue between a woman writer and her audience of mediation by a male critic and translator.